Little green men - Buckley, Christopher 1952- (Random House, 1999)
A comedy on a Washington TV pundit who is abducted by aliens and becomes a crusading UFO believer. In reality, the abduction was staged by the government to gain support for space research. By the author of Thank You for Smoking.
Keywords: Alien abduction -- Fiction; Unidentified flying objects -- Sightings and encounters -- Fiction; Washington (D.C.) -- Fiction; Humorous stories